2015
DOI: 10.13075/ijomeh.1896.00434
|View full text |Cite
|
Sign up to set email alerts
|

Residential exposure to environmental tobacco smoke, and its associates: Findings from the Global Adult Tobacco Survey in Poland

Abstract: Objectives: Expanding the information on exposure to environmental tobacco smoke (ETS) at home and its associates is of great public health importance. The aim of the current analysis was to evaluate associates of exposure to environmental tobacco smoke among economically active male and female adults in Poland in their place of residence. Material and Methods: Data on the representative sample of 7840 adults from the Global Adult Tobacco Survey (GATS) carried out in Poland in the years 2009 and 2010 were appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
1
2
0
2
Order By: Relevance
“…This study revealed that the proportion of non-smokers in Malaysia (27.9%) who were exposed to SHS at home was comparable to that in Brazil (27.9%) 13 and Ukraine (23.5%) 13 but lower than that reported 14 in China (67.3%), Philippines (44.8%), Bangladesh (43%) and Thailand (39.1%). On the other hand, the proportion of non-smokers that were exposed to SHS at their workplace was similar to that reported in the third (33%, year 2008) and fourth waves (29.9%, year 2009) of the International Tobacco Control survey in Malaysia 14 , as well as that reported in Poland (33.9%) 15 , but lower than that reported in Bangladesh (54.6%) 13 . These findings suggest that the SHS exposure in the workplace leveled off over the last 2 years in Malaysia 14 , and compared to other low- and middle-income countries, the level of SHS exposure among Malaysian non-smokers was moderate 13 .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This study revealed that the proportion of non-smokers in Malaysia (27.9%) who were exposed to SHS at home was comparable to that in Brazil (27.9%) 13 and Ukraine (23.5%) 13 but lower than that reported 14 in China (67.3%), Philippines (44.8%), Bangladesh (43%) and Thailand (39.1%). On the other hand, the proportion of non-smokers that were exposed to SHS at their workplace was similar to that reported in the third (33%, year 2008) and fourth waves (29.9%, year 2009) of the International Tobacco Control survey in Malaysia 14 , as well as that reported in Poland (33.9%) 15 , but lower than that reported in Bangladesh (54.6%) 13 . These findings suggest that the SHS exposure in the workplace leveled off over the last 2 years in Malaysia 14 , and compared to other low- and middle-income countries, the level of SHS exposure among Malaysian non-smokers was moderate 13 .…”
Section: Discussionsupporting
confidence: 77%
“…The present results show that female respondents are more likely to be exposed to SHS at home, which is in line with the findings reported in Bangladesh 10 and Thailand 16 . However, Kaleta et al 15 reported no such association among Polish adults. The gender differences in SHS exposure between Asian and Western countries 10,15,16 may be attributable to cultural differences.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…W skali globalnej ETS stanowi jednak problem dużej wagi nie tylko w miejscu pracy i miejscach publicznych, ale także w prywatnych domach. Badanie GATS wykazało, że w Polsce w miejscu pracy na ETS narażonych było 36% badanych, natomiast w miejscu zamieszkania -aż 59% [19,20]. Istnieją doniesienia, że wprowadzenie zakazu palenia tytoniu w miejscach pracy znacznie redukuje palenie wśród pracowników i bierną ekspozycję na dym tytoniowy także w prywatnych domach [20,21].…”
Section: Wyniki Przegląduunclassified
“…Badanie GATS wykazało, że w Polsce w miejscu pracy na ETS narażonych było 36% badanych, natomiast w miejscu zamieszkania -aż 59% [19,20]. Istnieją doniesienia, że wprowadzenie zakazu palenia tytoniu w miejscach pracy znacznie redukuje palenie wśród pracowników i bierną ekspozycję na dym tytoniowy także w prywatnych domach [20,21]. Dotychczas wykazano, że bierna ekspozycja na dym tytoniowy zwiększa ryzyko: n upośledzenia funkcji płuc -u osób narażonych na SHS w miejscu pracy w pomiarach spirometrycznych uzyskiwano wartość parametru nasilonej pierwszosekundowej objętości wydechowej (forced expiratory volume in one second -FEV 1 ) śred-nio o 2,7% niższą w porównaniu z wartością uzyskaną przed rozpoczęciem pracy [22], a w wyniku redukcji narażenia na SHS (po wprowadzeniu rozwiązań legislacyjnych zabraniających palenia tytoniu w miejscu pracy) u pracowników obserwowano istotną poprawę parametrów wentylacyjnych płuc w badaniach spirometrycznych [23,24]; n infekcji dróg oddechowych -dotychczas wykazano dodatnią korelację między narażeniem na SHS a zapadalnością na pneumokokowe zapalenie płuc i gruźlicę [25]; n przewlekłych schorzeń układu oddechowego, takich jak astma, przewlekłe zapalenie oskrzeli i przewlekła obturacyjna choroba płuc [23,[26][27][28] oraz zaostrzeń tych chorób -aż 69-78% pacjentów z astmą oskrzelową podaje, że narażenie na SHS powoduje u nich pogorszenie samopoczucia w wyniku nasilenia dolegliwości ze strony układu oddechowego [26,27]; dym tytoniowy zawiera w składzie wiele czynników drażniących, które stymulują komórki nabłonka oddechowego m.in.…”
Section: Wyniki Przegląduunclassified